THE EFFECT OF RETURN ON EQUITY (ROE), EARNINGS PER SHARE (EPS), AND DEBT TO EQUITY RATIO (DER) ON THE STOCK PRICES OF ENERGY SECTOR COMPANIES ON THE INDONESIA STOCK EXCHANGE - Gafiarty, Gafina Bunga; Samosir, Maralus; P Nainggolan, Ringkot; Siagian, Frisca L; Dewi , Diana Setiyo (Jurnal Akuntansi dan Perpajakan Jayakarta, 2025)
This study examines the effect of Return on Equity (ROE), Earnings per Share (EPS), and Debt to Equity Ratio (DER) on stock prices of energy sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2023. The background of the research stems from the inconsistency between financial performance recovery and fluctuating stock prices in the post-pandemic period. This study employs a quantitative approach with multiple linear regression. The results show that partially, only EPS has a significant effect on stock prices, while ROE and DER do not. However, simultaneously, all three variables significantly affect stock prices. The findings are relevant for investors and capital market analysts to reassess the importance of financial ratios in assessing stock valuation.